2019
DOI: 10.3390/rs11131604
|View full text |Cite
|
Sign up to set email alerts
|

An End-to-End Conditional Random Fields and Skip-Connected Generative Adversarial Segmentation Network for Remote Sensing Images

Abstract: Semantic segmentation is an important process of scene recognition with deep learning frameworks achieving state of the art results, thus gaining much attention from the remote sensing community. In this paper, an end-to-end conditional random fields generative adversarial segmentation network is proposed. Three key factors of this algorithm are as follows. First, the network combines generative adversarial network and Bayesian framework to realize the estimation from the prior probability to the posterior pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Some studies make CRFs differentiable [39] or turn them into a recurrent network [40] to train with the network end-to-end. He et al [41] integrated a skip-connected encoder-decoder network structure and CRF layer to implement end-to-end network training, and the result was improved by taking more information into account. To reduce salt-and-pepper noise, Zhao et al [11] transformed image pixel labels into semantic segments and presented a semantic segment-based CRF method to effectively exploit the contextual relationships between different categories of ground objects.…”
Section: Semantic Segmentation For High-resolution Aerial Imagesmentioning
confidence: 99%
“…Some studies make CRFs differentiable [39] or turn them into a recurrent network [40] to train with the network end-to-end. He et al [41] integrated a skip-connected encoder-decoder network structure and CRF layer to implement end-to-end network training, and the result was improved by taking more information into account. To reduce salt-and-pepper noise, Zhao et al [11] transformed image pixel labels into semantic segments and presented a semantic segment-based CRF method to effectively exploit the contextual relationships between different categories of ground objects.…”
Section: Semantic Segmentation For High-resolution Aerial Imagesmentioning
confidence: 99%
“…Moreover, the term abs means to take the absolute value of the amount in the associated brackets. In the paper [35], g loss contains a cross-entropy loss term, an L1 loss term, and an adversarial loss term g GAN . From Equations 3and 6, it can be found that the L1 loss calculates the absolute difference between the labels, and the cross-entropy is the degree of correlation between the label probabilities.…”
Section: Loss Functionmentioning
confidence: 99%
“…Luc et al [28] first used GAN to image segmentation for the purpose of enhancing long-range spatial label contiguity without increasing the complexity of the model used in the test. Subsequently, a variety of GAN-based segmentation methods [29][30][31][32][33][34][35] were proposed. Zhu et al [29] proposed an end-to-end network with the trained adversarial deep structure to improve the robustness of a small data model and prevent over-fitting.…”
Section: Introductionmentioning
confidence: 99%
“…To complete the calculations, previous studies have used approximate calculations [60,61], reduction of the number of samples involved in modeling [62,63], and introduced conditional independence [64][65][66]. However, in doing so, the performance of the CRFs gets reduced [67]. To combine a CNN and CRFs, and achieve end-to-end training, several studies [67][68][69] have converted the CRF into an iterative calculation, while others [64] have converted the CRF into a convolution operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, in doing so, the performance of the CRFs gets reduced [67]. To combine a CNN and CRFs, and achieve end-to-end training, several studies [67][68][69] have converted the CRF into an iterative calculation, while others [64] have converted the CRF into a convolution operation.…”
Section: Introductionmentioning
confidence: 99%